DAMPAK MENONTON SERIAL ANIMASI DORA THE EXPLORER TERHADAP TINGKAT KONSENTRASI SISWA SEKOLAH DASAR - Wakhyudin, Husni; Ningrum, Dian Novita (Universitas Muria Kudus, 2018)
The purpose of this research is to know the impact of watching animated series Dora The Explorer to the level of student concentration in SD Negeri Tinjomoyo 01 Semarang. The approach used in this research is qualitative descriptive research approach that is research that describes events or phenomena with data in the form of information or words. Qualitative approach is expected to produce a deep description of the words, writings and behavior observed from an individual, groups, communities and organizations in a given contextual situation studied in a comprehensive, holistic and holistic perspective. This approach is used to describe and describe the focus of research, namely the analysis of the impact of watching the animated series Dora The Explorer to the level of student concentration. The emergence of student learning behavior in this study researchers can describe as follows: the emergence of student cognitive behavior as many as 30 students, as many as 30 students, the appearance of psychomotor behavior of students as much as 35 students and the appearance of language behavior as many as 29 students. So it can be said that the concentration level of students when the animated series Dora The Explorer animation is high.